PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Ryan Julian; Estralita Trisnawati; Yustina Peniyanti Jap (Jurnal Kontemporer Akuntansi, 2024)
The research conducted aims to analyze and find the effect of profitability, capital structure, liquidity and companysize on firm value in Food and Beverage sub-sector companies on the Indonesia Stock Exchange for the period2017–2020. The research method that was be used in this study is a quantitative descriptive method andverification. The research samples were 25 companies in the food and beverage sub-sector on the Indonesia StockExchange (IDX) with 100 observations. Testing the data using panel data regression data analysis with Eviews. Theresults of the research show that profitability (ROA) has a positive and significant effect on firm value. Capitalstructure (DER) and firm size (SIZE) have a negative and significant effect on firm value. Meanwhile, liquidity (CR)has no effect on company value in food and beverage sub-sector companies on the IDX for the 2017-2020 period.